The Gambia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper describes the recent economic developments in The Gambia. The paper highlights that the economic performance of The Gambia deteriorated sharply in 2002, as sparse rainfall led to a decline of one-third in agricultural output. Real GDP shrank by 3 percent. However, sectors other than agriculture fared reasonably well: the tourism sector benefited from greater political stability and improved competitiveness. The paper analyzes The Gambia's external position and vulnerabilities to shocks. It also elaborates data deficiencies in The Gambia's balance of payments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet